The human parasite Loa loa in cytokine and cytokine receptor gene knock out BALB/c mice: survival, development and localization - Tendongfor Nicholas; Wanji Samuel; Ngwa Julius C; Esum Mathias E; Specht Sabine; Enyong Peter; Matthaei Klaus I; Hoerauf Achim (Parasites & Vectors, 2012)
Abstract Background Immunological mechanisms involved in the survival and development of human filarial species in the vertebrate host are poorly known due to the lack of suitable experimental models. In order to understand the role of cytokines in the survival and development of filarial larvae in the vertebrate host, we infected different strains of BALB/c mice deficient in a number of cytokine or cytokine receptor genes with Loa loa. The survival and development of larvae were monitored. Methods BALB/c mice genetically deficient in IL-4R, IFN-γ, IFN-γ/IL-5, IL-5, and IL-4R/IL-5 cytokine or cytokine receptor genes were infected with a human strain of L. loa and necropsies were performed at different time intervals up to 70 days post infection to monitor the survival and development of L. loa larvae. The larvae were teased out of the skin, muscles, peritoneal and pleural cavities, heart and lung tissues. The length and width of the recovered larvae were measured to assess their growth. Results In mice deficient for IL-4R, IFN-γ, IFN-γ/IL-5, IL-5 and IL-4R/IL-5, the larvae survived up to 5, 20, 40, 50 and 70 days respectively. Worms recovered 70 days post infection in IL-4R/IL-5 DKO mice were young adults and measured 10.12 mm in length and 0.1 mm in width. Overall, 47% of larvae were recovered from subcutaneous tissues, 40% from muscles, 6% from the peritoneal cavity and 4% from the pleural cavity, lungs and heart. Conclusion L. loa exhibits a differential survival and development in different strains of cytokine or cytokine receptor gene knockout mice with IL-4R and IL-5 playing critical roles in the host resistance to L. loa infection. The knock out BALB/c mouse therefore represents a useful tool to explore the key effectors of adaptive immunity involved in the killing of the L. loa parasite in a mammal host.